Automation of Analysis And Structural-Parametric Synthesis of Planetary Gearboxes With Two Degrees Of Freedom - Volontsevich, Dmitriy; Pasechnyi, S. (Austria, Sankt Lorenzen, 2016)
The planetary gears in transmissions of non-rail ground transport vehicles are widely used. Mostly, all modern automatic transmissions are based on the planetary mechanisms. The design of the optimal schematic diagram and the calculations of the parameters is extremely complicated. Moreover, this process is automated particularly. The design of kinematic schemes, which based on the selected linkages is the most complicated process for automatization. The algorithm and software for analysis and structural-parametric synthesis of planetary gearboxes with two degrees of freedoms is considered. The suggested approach can be applied to elementary planetary gears and systems with two or more satellites and double-wheel gears. The software is implemented only for planetary gearboxes with two degrees of freedom. The software for the planetary gearboxes with three degrees of freedom is implemented at the nearest time. The quantitative criteria of quality for estimation of planetary gearboxes quality are developed. These criteria allow to numerically evaluating the following characteristics of planetary gearboxes as the presence and magnitude of the circulating power, the relative magnitude of the torque on brakes and clutches, the relative speed of rotation of the central units, satellites and open-loop brakes and clutches and much more. The generated kinematics schemes are compared according to selected multiple criteria or integrated criteria with weights coefficients.
Keywords: planetary gearboxes; analysis and structural-parametric synthesis; quantitative criteria of quality